The German version of the generalized expectancies for negative mood regulation scale: a construct validity study - Backenstraß, Matthias; Joest, Katharina; Gehrig, Nicole; Pfeiffer, Nils; Mearns, Jack; Catanzaro, Salvatore J. (European journal of psychological assessment, 2010)
The Generalized Expectancies for Negative Mood Regulation (NMR) Scale has been developed to assess beliefs about one’s ability to do something to feel better when emotionally upset. One aim of the present study was to replicate convergent and discriminant relationships with constructs such as coping behavior, emotion regulation strategies, and social desirability using the German version of the NMR Scale. Furthermore, the series of studies reported in this paper examined the incremental validity of the NMR Scale. The correlations found between the NMR Scale and the studied constructs are in accordance with theoretical assumptions and replicate results found with the original English language NMR Scale. Tests of incremental validity showed that the German version of the NMR Scale explained variance in depressive symptoms beyond that explained by task-oriented, emotion-oriented, and avoidance-oriented coping; emotion regulation strategies; locus of control variables; and self-efficacy. Finally, depressive patients were found to have lower NMR expectancies than a healthy control group - even when the severity of depressive symptoms was statistically controlled. Thus, the present study confirmed the validity of the German version of the NMR Scale and, by analyzing its incremental validity, emphasized the significance the NMR construct has for emotion regulation research.
Gesehen am 29.11.2022